Hair follicle growth by stromal vascular fraction-enhanced adipose transplantation in baldness - Perez-Meza D (Dove Medical Press, 2017)
David Perez-Meza,1 Craig Ziering,2 Marcos Sforza,3 Ganesh Krishnan,4 Edward Ball,5 Eric Daniels6 1Ziering Medical, Marbella, Spain; 2Ziering Medical, Los Angeles, CA, USA; 3The Hospital Group, Bromsgrove, Worcestershire, 4Ziering Medical, Birmingham, 5Ziering Medical, London, UK; 6Kerastem Technologies, San Diego, CA, USA Abstract: Great interest remains in finding new and emerging therapies for the treatment of male and female pattern hair loss. The autologous fat grafting technique is >100 years old, with a recent and dramatic increase in clinical experience over the past 10–15 years. Recently, in 2001, Zuk et al published the presence of adipose-derived stem cells, and abundant research has shown that adipose is a complex, biological active, and important tissue. Festa et al, in 2011, reported that adipocyte lineage cells support the stem cell niche and help drive the complex hair growth cycle. Adipose-derived regenerative cells (also known as stromal vascular fraction [SVF]) is a heterogeneous group of noncultured cells that can be reliably extracted from adipose by using automated systems, and these cells work largely by paracrine mechanisms to support adipocyte viability. While, today, autologous fat is transplanted primarily for esthetic and reconstructive volume, surgeons have previously reported positive skin and hair changes posttransplantation. This follicular regenerative approach is intriguing and raises the possibility that one can drive or restore the hair cycle in male and female pattern baldness by stimulating the niche with autologous fat enriched with SVF. In this first of a kind patient series, the authors report on the safety, tolerability, and quantitative, as well as photographic changes, in a group of patients with early genetic alopecia treated with subcutaneous scalp injection of enriched adipose tissue. The findings suggest that scalp stem cell-enriched fat grafting may represent a promising alternative approach to treating baldness in men and women. Keywords: stem cell, alopecia, adipose, stromal vascular fraction, transplantation